POLA PENERBITAN JONI TAMKIN BIN BORHAN DALAM BIDANG EKONOMI ISLAM: KAJIAN BIO-BIBLIOMETRIK (Pattern of Publication of Joni Tamkin Bin Borhan in Islamic Economic: A Bio-bibliometric Study) - Abdul Hamid, Faisal @ Ahmad Faisal; Hussin, Nurul Afiqah (Journal of Al-Tamaddun, 2020)
This article discusses the achievements of Professor Dr Joni Tamkin Borhan in producing scientific publications. He was a Professor in Islamic economics at the Department of Shariah and Economics, Academy of Islamic Studies, University of Malaya. His publication patterns in various forms such as books, journal articles and others are discussed in this article, as well as the use of language and his kinds of collaboration with other writers’ figures in the production of scientific works. Prior to that, this paper explains brief biodata about himself, his contributions in academic and also his involvement in community. The data was collected from his own UM-Expert database before he passed away. This database is used to share with others of his academic activities and also used as evaluation for his achievements by UM. In addition, interviews with his wife were also conducted for additional information and confirmation of some relevant facts. In conclusion, he was an active professor in the field of scientific publications and did contribute greatly either directly as an academician or through hi role as advisor to financial institutions in the country. This paper proofs that he is a good example of other academicians especially in the field of Islamic studies and Islamic economy.